1999
DOI: 10.1007/s004310051184
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception in infants and children: feasibility of ambulatory management

Abstract: To evaluate the ambulatory management of ileo-colic intussusception in infants and children, a retrospective study over 3 years of 113 children treated for ileo-colic intussusception in a paediatric emergency department was undertaken with the aim of shortening the length of stay. A total of 113 children aged 10 days to 9 years (median 12 months) were treated for intussusception between January 1993 and December 1996. None had septic shock or peritoneal aeric effusion. Barium enema reduction was attempted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 22 publications
0
16
0
5
Order By: Relevance
“…In a study by Le Masne et al, 20 54% of 92 children were managed as outpatients after successful reductions, with no subsequent adverse events other than an uncomplicated recurrence of the intussusception (16%). In another study by Gilmore et al, 14 82% of 56 children were discharged after a brief observation period of 7 hours and also had no adverse events other than recurrence (5.3%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Le Masne et al, 20 54% of 92 children were managed as outpatients after successful reductions, with no subsequent adverse events other than an uncomplicated recurrence of the intussusception (16%). In another study by Gilmore et al, 14 82% of 56 children were discharged after a brief observation period of 7 hours and also had no adverse events other than recurrence (5.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of intussusception has evolved from primarily operative management to the preference for non-operative reduction with either air or barium contrast. Non-operative reductions of intussusception had been shown to decrease length of hospitalization, shorten recovery, and reduce the risk of complications associated with major abdominal surgery [15]. Reports from some developing countries however indicate that for some ill-defined reasons, operative treatment is still routinely performed for intussusceptions [16-18].…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of intussusception are idiopathic and currently the initial management is pneumatic or barium reduction. The recurrence rate for non-surgical reduction is reported to be approximately 5% to 10% [3,4]. A large survey found that almost 50% of the instances of recurrent intussusception occurred within the 1st week of life [1,2], and is de®ned as early recurrent intussusception (ERI).…”
mentioning
confidence: 99%